(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Effect of ZnO/PbO and Fe/SiO2 on the viscosity of the PbO-ZnO-Fe3O4-SiO2-CaO slag was measured using the rotating spindle method. The slag viscosity decreased with decreasing ZnO/PbO mass ratio because of depolymerization of the silicate structures. The viscosity decreased with increasing Fe/SiO2 mass ratio as experimental temperature was above 1623 K, while the viscosity increased significantly with the increase of Fe/SiO2 as the experimental temperature below 1623 K because of phase transition and change of slag melting point. According to XRD analysis of as-quenched slag, the spinel and zincite phase increased with increasing Fe/SiO2. The increasing ZnO/PbO and Fe/SiO2 could enhance the crystallization capacity of the slag. FTIR analysis revealed that the degree of polymerization of the as-quenched slags decreased with decreasing ZnO/PbO and increasing Fe/SiO2. The temperature dependencies of the viscosity on ZnO/PbO and Fe/SiO2 were investigated, and the apparent activation energies of each system were found to be between 169.5 to 227.4 KJ/mol, and 151.1 to 676.4 KJ/mol, respectively.